2020
DOI: 10.1111/liv.14642
|View full text |Cite
|
Sign up to set email alerts
|

ABCB11 deficiency presenting as transient neonatal cholestasis: Correlation with genotypes and BSEP expression

Abstract: Background & Aims: ABCB11 deficiency presenting in infancy is believed generally to manifest as persistent/progressive cholestasis. We describe a group of patients with biallelic ABCB11 variants whose disorder manifested as transient neonatal cholestasis (TNC). Methods: Neonatal intrahepatic cholestasis in 68 children (31 males) with biallelic predictedly pathogenic variants (PPV) in ABCB11 was classified as transient (TNC group, n = 23, 11 males), intermittent (benign recurrent intrahepatic cholestasis [BRIC]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…For instance, mutations in the ABCA4 gene contribute to Stargardt macular degeneration, progressive familial intrahepatic cholestasis is caused by ABCB11 deficiency, and ABCC7, which is also known as cystic fibrosis transmembrane conductance regulator, is linked to cystic fibrosis. [8][9][10] ABC transporters are also involved in absorbing, distributing, and excreting the drugs and their metabolites, 11 which is associated with drug resistance of cancer cells. For example, ABCB1 is confirmed to be involved in multidrug resistance (MDR) and it can also be named MDR.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mutations in the ABCA4 gene contribute to Stargardt macular degeneration, progressive familial intrahepatic cholestasis is caused by ABCB11 deficiency, and ABCC7, which is also known as cystic fibrosis transmembrane conductance regulator, is linked to cystic fibrosis. [8][9][10] ABC transporters are also involved in absorbing, distributing, and excreting the drugs and their metabolites, 11 which is associated with drug resistance of cancer cells. For example, ABCB1 is confirmed to be involved in multidrug resistance (MDR) and it can also be named MDR.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with BSEP1 genotype (p.D482G and p.E297G) have residual BSEP functionality and thus have a milder phenotype as compared to patients exhibiting BSEP2/BSEP3 genotype. There is wide geographical variations in genotype with the commonest mutations found in a study from Shanghai being c.145C>T (p.Gln49Ter) and c.2594C>T (p.Ala865Val)[ 21 ]. Severe phenotypes are often associated with mutations leading to premature protein truncation or failure of protein production.…”
Section: Bsep Deficiencymentioning
confidence: 99%
“…Hence, close monitoring of these children particularly those carrying 2 null mutations is essential[ 22 ]. Children with transient neonatal cholestasis harbour non-null variants, express immune-histochemically detectable BSEP and have better outcomes[ 21 ].…”
Section: Bsep Deficiencymentioning
confidence: 99%
“…Similarly, Li et al showed that carriers of biallelic non‐null mutations of ABCB11 , encoding for bile salt export protein (BSEP), present more frequently with transient neonatal cholestasis, while patients with more severe mutations have lower BSEP expression and tend to develop progressive FIC type 2 13 …”
Section: Figurementioning
confidence: 99%